Avaliação da polarização de macrófagos durante infecção por Schistosoma mansoni Sambon,1907 - FONSECA, Irlla Correia Lima Licá (2023)
Human schistosomiasis is a neglected parasitic disease of significant public health relevance caused by trematode helminths of the species Schistosoma mansoni. Macrophages play a crucial role during S. mansoni infection and can adopt different phenotypes. Despite the importance of macrophages in infection control, the involvement of functional macrophage types in schistosomiasis remains poorly defined. This study was divided into two chapters with the aim of expanding prospective investigations into macrophage polarization in schistosomiasis. In Chapter 1, we provide a brief review highlighting diverse pathways of molecule and/or macrophage activation and polarization during the disease. This review is based on original and review articles obtained from major databases, including Scopus, Google Scholar, ACS, PubMed, Wiley, Scielo, Web of Science, LILACS, and ScienceDirect. The results underscore the significance of S. mansoni and Schistosoma japonicum antigens in macrophage polarization, as they exert immunomodulatory effects at different disease stages. In Chapter 2, the objective was to assess macrophage responses in the presence of S. mansoni cercariae and adult worms in vitro, as well as the expression of M1 and M2 macrophage markers in hepatic tissue in a murine model of chronic S. mansoni infection. In vitro assays employed macrophages (RAW 264.7) cultured at a concentration of 1x106 /mL, including non- polarized (M0) macrophages, M1 macrophages previously polarized with LPS (2000 ng/mL) and IFN-γ (100 ng/mL), and M2 macrophages with IL-4 (400 ng/mL) and IL-13 (200 ng/mL). These cells were co-cultured with cercariae (10 cercariae/well) or adult worms (2 worms/well) of S. mansoni. After 24 hours and 72 hours, cercariae and adult worm viability, respectively, were assessed. Furthermore, we investigated whether adult worms could influence the polarization of previously activated macrophages by quantifying iNOS and Arginase expression, nitric oxide production, cytokine production, and Arginase activity. In in vivo studies, M1 and M2 macrophage expression in the hepatic tissue of mice infected with 50 cercariae of S. mansoni after 90 days of infection was evaluated, using uninfected mice as controls. The in vitro results revealed that both non-polarized (M0) and M1 macrophages displayed cytotoxicity against S. mansoni cercariae and adult worms. Interestingly, adult worms had the capacity to potentiate the polarization of previously stimulated macrophages, inducing an M1 profile in M0 macrophages. In vivo, there was a significant increase in the expression of specific markers associated with M1 and M2 profiles in the hepatic tissues of infected mice. Furthermore, we observed that M2 macrophage expression exceeded that of M1 macrophages in the hepatic tissue of these infected animals, and this predominance of M2 macrophages was correlated with a reduction in the number of hepatic granulomas. Importantly, our investigation revealed that neither M1 nor M2 macrophages significantly influenced liver weight or hepatic granuloma size. In summary, macrophages can adopt different profiles at each stage of S. mansoni infection, mitigating host damage while potentially enhancing parasite survival. These findings are valuable for the development of vaccines and immunotherapies against schistosomiasis, as they elucidate the mechanisms by which macrophages can contribute to infection protection or pathogenesis.